2019
DOI: 10.3389/fmicb.2019.02877
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Enterococcus Phage vB_EfaS_HEf13 Has Broad Lytic Activity Against Clinical Isolates of Enterococcus faecalis

Abstract: Enterococcus faecalis is a Gram-positive, facultative anaerobic bacterium frequently found in the gastrointestinal tract, oral cavity, and periodontal tissue. Although it is considered a commensal, it can cause bacteremia, endocarditis, endodontic infections, and urinary tract infections. Because antibiotics are cytotoxic not only to pathogens, but also to health-beneficial commensals, phage therapy has emerged as an alternative strategy to specifically control pathogenic bacteria with minimal damage to the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 61 publications
(67 reference statements)
0
47
0
Order By: Relevance
“…Therefore, we suggest that further molecular characterization of replication enzymes may be of special interest and can lead to discoveries of novel properties of these proteins, especially since our knowledge of the variability and diversity of phage-encoded DNA polymerases is relatively poor. In fact, recent reports on the characterization of other enterococcal phages indicated that this group of viruses may have interesting and unique features, pointing to their high biodiversity [ 39 , 41 , 42 , 43 , 44 , 45 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that further molecular characterization of replication enzymes may be of special interest and can lead to discoveries of novel properties of these proteins, especially since our knowledge of the variability and diversity of phage-encoded DNA polymerases is relatively poor. In fact, recent reports on the characterization of other enterococcal phages indicated that this group of viruses may have interesting and unique features, pointing to their high biodiversity [ 39 , 41 , 42 , 43 , 44 , 45 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this systematic review, three studies discussed some treatment options to reduce or remove E. faecalis from the root canal system and the periradicular area [23][24][25]. Antibiotic medications were widely used for the treatment and prevention of E. faecalis caused by many pathogenic bacteria.…”
Section: Treatment Options Against E Faecalismentioning
confidence: 99%
“…Other studies discussed novel treatment techniques using newly isolated phages for targeting E. faecalis strains from the oral cavity. Lee D et al found that phage HEf13 has high lytic activity against human dentin, which suggests the effectiveness of using phage HEf13 as a dental therapeutic agent against E. faecalis-related apical periodontitis [24]. A recent study conducted by Ghorbanzadeh A et al in 2020 found three effective disinfection methods for the partial elimination of E. faecalis biofilm [25].…”
Section: Treatment Options Against E Faecalismentioning
confidence: 99%
“…Morphological characterization revealed that PHB08 had a rectangular head (length 124 mm ± 5, width 61 mm ± 5) and a long tail (158 mm ± 5) ( Figure 1 a). These morphological characteristics were similar to Enterococcus phage HEf13 [ 55 ] and phage IME-EF1 [ 56 ]. The phylogenetic analysis showed that PHB08 was closely related to phage SAP6 (isolated from South Korea) ( Figure 3 c).…”
Section: Discussionmentioning
confidence: 73%
“…Potential bactericidal ability at low MOI was similar to those of the single phage 13076 and phage 14028 [ 36 ]. Characterizations on the temperature and pH stabilities showed that PHB08 had relatively excellent stability at temperatures between 4 and 60 °C, and pH between 5.0 and 9.0, which displays similar characteristics to those of the other E. faecalis phages, such as Enterococcus phage vB_EfaS_HEf13 [ 55 ], and Enterococcus phage EF-P10 [ 57 ]. One-step growth curve revealed that PHB08 had a latency of 10 min and a high-speed growth period of 50 min with an average burst size of 64 phage particles per infected cell after 70 min at 37 °C ( Figure 1 d), which is in agreement with the generally reported average burst of phages (about 30-122 phage particles per infected) [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%